Kant and the enhancement debate: Imperfect duties and perfecting ourselves. (3rd July 2021) - Chance, Brian A.
Abstract: This essay develops a Kantian approach to the permissibility of biomedical physical, cognitive, and moral enhancement. Kant holds that human beings have an imperfect duty to promote their physical, cognitive, and moral perfection. While an agent's individual circumstances may limit the means she may permissibly use to enhance herself, whether biomedically or otherwise, I argue (1) that biomedical means of enhancing oneself are, generally speaking, both permissible and meritorious from a Kantian perspective. Despite often being equally permissible, I also argue (2) that enhancing oneself by more traditional means is, generally speaking, more meritorious (and involves the display of more virtue) than enhancing oneself by biomedical means. Nevertheless, since Kant does not fault agents for acting less meritoriously (or for displaying less virtue) than they otherwise could, I also argue (3) that those who opt for permissible biomedical enhancement over more traditional forms are not blameworthy for doing so. I also consider and reject several objections to these claims, including that biomedical enhancements (1) are too passive to count as actions by the agent who enhances herself, (2) involve a failure of the agent to treat her humanity as an end in itself or to show proper respect for her dignity, (3) might be undertaken on the basis of motives that undermine their permissibility, (4) are likely to exacerbate existing social and economic inequalities in ways that do the same, and (5) in their moral form are incompatible with Kant's conception of duty and human freedom.